Development of neural engineering methods for objective assessment of cognitive processing based on Gait Data : an analysis of a truly nationally representative cohort of older adults - Killane, Isabelle (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2015)
Knowledge of the brain substrates and neural networks at play during gait are not well understood. However, strong associations between gait and cognitive function have been found in literature. Examining this relationship further may allow inferences to be drawn through investigating the contributions of specific elements of cognitive function to gait. This thesis outlines the role that cognitive function has been found to play in gait performance in older adults and early stage cognitive impairment. Gait speed has been examined in detail due to its association with survival[2] and activities of daily living[3].
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin